2015
DOI: 10.1063/1.4921537
|View full text |Cite
|
Sign up to set email alerts
|

Spin-glass-like behavior and negative thermal expansion in antiperovskite Mn3Ni1−xCuxN compounds

Abstract: Articles you may be interested inEffect of Cu substitution on the magnetic and dielectric properties of La2NiMnO6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…In this Rapid Communication, we demonstrate that the AHE could indeed be realized in manganese nitrides, by studying the Mn 3 NiN system [12,13,17,18]. We first found that in stoichiometric Mn 3 NiN, a weak signal of AHE is observed below the noncollinear AFM ordering temperature of 180K, yet disappeared as the temperature further decreases.…”
mentioning
confidence: 96%
“…In this Rapid Communication, we demonstrate that the AHE could indeed be realized in manganese nitrides, by studying the Mn 3 NiN system [12,13,17,18]. We first found that in stoichiometric Mn 3 NiN, a weak signal of AHE is observed below the noncollinear AFM ordering temperature of 180K, yet disappeared as the temperature further decreases.…”
mentioning
confidence: 96%
“…25 The magnetisms of Ga 0.9 Fe 3.1 N was analyzed by Mössbauer studies and understood as a kind of "cluster magnetism" where 13-atom Fe clusters are incorporated in a metallic gallium sublattice. 26,27 Spin-glass behavior has only been found in several Mn-, [12][13][14][15][16] Co-, 17 Ni-, 17 and Cr-18 based ternary nitrides. Up to the present day, however, there are no investigations of spin-glass behavior in A x Fe 4−x N. The only known Fe-based spin glass is the carbide with the reported composition SnFe 3 C that exhibits a static glassy transition temperature of 20.3 K. 19 In the present study, a comprehensive magnetic characterization of Sn 0.9 Fe 3.1 N is carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Both nitrides and carbides adopt a simple antiperovskite-like structure in space group Pm3;¯m and feature remarkable properties, such as giant magnetoresistance effect (GMR), 2-4 negative or zero thermal expansion (NTE or ZTE), [5][6][7] nearly zero temperature coefficient of resistance (TCR), 8,9 giant magnetostriction (MS), 10 giant barocaloric effect, 11 spin-glass behavior, [12][13][14][15][16][17][18][19] and phase separation. 20 These properties have been mostly found in Mn-based nitrides (AMn 3 N) [5][6][7][8][9][10][11][12][13][14][15][16] but recent investigations also focused on Ni-, 17 Co-, 17 and Cr- systems, a frustrated system was described for the amorphous binary alloy Fe x Sn 1−x where structural disorder comes together with site disorder. 25 The magnetisms of Ga 0.9 Fe 3.1 N was analyzed by Mössbauer studies and understood as a kind of "cluster magnetism" where 13-atom Fe clusters are incorporated in a metallic gallium sublattice.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3], near-zero temperature coefficient of resistivity (TCR) [4,5,6], magnetostriction [7], spin-glass (SG) behavior [8,9,10] and magnetocaloric effect [11,12]. It has been found that these interesting physical properties are sensitive to the number of the valence electrons of metal X located at the corners of antiperovskite unit cell, which contributes itinerant electrons at the Fermi level [13].…”
Section: Introductionmentioning
confidence: 99%